Organisational barriers to institutional change: The case of intelligence in New Zealand policing. Issue 4 (21st June 2022) - Lindsay, Angus; Bradley, Trevor; Mackenzie, Simon
Abstract: Over recent decades Intelligence‐led Policing (ILP) has become a central component of the attempts by New Zealand Police (NZP) to engineer a transformative shift away from 'reactive' policing to more 'proactive' approaches to crime reduction. ILP appeared to offer an effective response to increasingly complex crime problems, an expanded 'mission' and growing public demand, by placing crime intelligence central to decision making. As part of an international study exploring police intelligence, we conducted 20 in‐depth semi‐structured interviews with Police Intelligence staff at all levels of the police hierarchy. Our findings highlight five critical barriers to implementing a successful ILP project in New Zealand. We suggest ILP has not delivered its promised effect of catalysing a major reorientation of the modes of frontline policing or its delivery and argue that this is due to the structural resilience of traditional police cultural reluctance to allow long‐established practice and procedural norms to be fundamentally changed.